Straight and crooked thinking - Thouless, Robert H. (Robert Henry), 1894-1984.; Thouless, C. R. (London : Hodder Education, 2011)
PHILOSOPHY. This new edition of a timeless classic demonstrates how the use of clear, rational thinking and logic can win any argument, however emotionally charged the topic in question. It describes the typical flaws of reasoning in argument and shows how language can be used to deceive - and how to avoid being deceived. It will show you how, by learning what is 'straight', rational language, and clear thought, you can disentangle emotionally charged rhetoric and hold your own in any argument or debate, no matter how challenging. Although written nearly 80 years ago, this book proves that certain principles remain timeless; it has shown many thousands over the decades how to cope with media spin and distorted reasoning - and now it will do the same for you.
Keywords: Logic; Communication; Thought and thinking